Iron-catalyzed C–C bond formation via cross dehydrative coupling reaction of N-heterocyclic aminols with electron rich arenes: facile access to C4-aryl-dihydroquinazolines. Issue 6 (11th February 2016) - Arun Kumar, R.; Srinivasulu, A.; Saidulu, G.; Santhosh Kumar, P.; Sridhar, B.; Rajender Reddy, K.
Abstract: The direct coupling of sp 3 C–OH bond of N -heterocyclic aminols with sp 2 C–H bond of electron rich arenes have been achieved via iron catalyzed dehydrative cross coupling strategy. This novel protocol provides an efficient and straight forward route to access biologically important C4-aryl-3, 4-dihydroquinazoline derivatives through the reaction of C4-hydroxy-3, 4-dihydroquinazoline/aminol with phenol and aniline derivatives under mild reaction conditions. Graphical abstract: